Reactive oxygen species responsive nanomotors for gene edited metabolic disruption and immunotherapy - Zhiyong Liu; Xiaowei Luan; Qianglan Lu; Shurong Qin; Fei Zeng; Zhi Li; Bangshun He; Yujun Song (Nature Communications)
Abstract While gene-editing-based tumor therapy holds promise, conventional passive-diffusion vectors face limited penetration in dense solid tumors. Here, we developed a ROS-driven gene editing nanomotor (RDN@PL), which takes hemin as the core and encapsulates CRISPR/Cas9 plasmids targeting LDHA (A glycolysis key enzyme). In tumor microenvironments, RDN@PL consumes extracellular ROS to fuel self-diffusiophoresis, achieving higher intratumoral accumulation than passive particles. Upon internalization, heme oxygenase-1 (HO-1) degrades RDN@PL, releasing CO and plasmids. LDHA knockout suppresses glycolysis while CO elevates mitochondrial ROS, which triggers apoptosis by disrupting metabolism and enhancing immunity. Simultaneously, extracellular ROS depletion by non-internalized nanomotors reverses immunogenic cell death (ICD) inhibition, enhancing CD8+ T cell infiltration in tumor. The Janus nanomotor enables extracellular ROS scavenging and intracellular ROS increment via HO-1-responsive cargo release and gene editing. This multi-level intervention strategy demonstrates 93.9 % tumor growth suppression in solid tumor models, providing a blueprint for engineering intelligent nanovesicles in precision oncology.